2018
DOI: 10.1152/jn.00477.2018
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the sensorimotor components of cybersickness

Abstract: The user base of the virtual reality (VR) medium is growing, and many of these users will experience cybersickness. Accounting for the vast inter-individual variability in cybersickness forms a pivotal step in solving the issue. Most studies of cybersickness focus on a single factor (e.g., balance, sex, vection), while other contributors are overlooked. Here, we characterize the complex relationship between cybersickness and several measures of sensorimotor processing. In a single session, we conducted a batte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 102 publications
3
57
0
2
Order By: Relevance
“…All other correlations between objective and subjective indices were non-significant. While the lack of strong correlation between the two measurement classes was unexpected, discrepancies between postural and subjective measures of vection have been reported before (Delorme & Martin, 1986;Fujii et al, 2019;Kawakita et al 2000;Palmisano et al, 2014;Weech et al, 2018). Our finding reiterates the need to concurrently evaluate objective and subjective vection indices in studies such as these, as evidence is accruing that there may be a major dissociation in the results obtained by these two approaches to measuring the 'same' percept.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…All other correlations between objective and subjective indices were non-significant. While the lack of strong correlation between the two measurement classes was unexpected, discrepancies between postural and subjective measures of vection have been reported before (Delorme & Martin, 1986;Fujii et al, 2019;Kawakita et al 2000;Palmisano et al, 2014;Weech et al, 2018). Our finding reiterates the need to concurrently evaluate objective and subjective vection indices in studies such as these, as evidence is accruing that there may be a major dissociation in the results obtained by these two approaches to measuring the 'same' percept.…”
Section: Discussionsupporting
confidence: 64%
“…Vection is accompanied by postural reflexes that indicate the engagement of motor strategies that aim to maintain stable control of the body during perceived self-motion (Berthoz et al, 1979). Recent evidence suggests that postural excursions during vection hold strong predictive power in models that classify susceptibility to motion sickness at the individual level (Keshavarz et al, 2015;Weech et al, 2018).Several other insights have been provided by studies on vection, including the neural basis of self-motion perception (e.g., Brandt et al, 1998;Kovács et al, 2008;Wada et al, 2016) and the relationship between visual eccentricity and self-motion (Johansson; Post, 1988;Nakamura & Shimojo, 1998). Studies of vection have an applied focus: Recently, the possibility of improving virtual reality experiences using vection has been investigated by several groups (Nakamura et al, 2016;Riecke, 2010;Riecke et al, 2015;Weech & Troje, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the second part of the study, participants played 30 min of a VR application that has previously been identified as highly nauseogenic (e.g., Weech et al, 2018b), consisting of a zerogravity space-walk simulation (ADR1FT, Three One Zero). The VR environment was presented with a head mounted display (Rift CV1, Oculus VR, Menlo Park, CA; 90 Hz refresh rate, 1080 × 1200 resolution per eye) and the environment was rendered by a high-end graphics card (NVIDIA GTX1070).…”
Section: Virtual Realitymentioning
confidence: 99%
“…Second, we asked participants to report subjective linear vection strength while they were exposed to radially-expanding optic flow. Vection has been implicated as a strong predictor for cybersickness (Keshavarz et al, 2015;Weech et al, 2018b; but c.f. Webb and Griffin, 2002) and as such, we assessed vection and its association with cybersickness and indices of sensory re-weighting.…”
Section: Introductionmentioning
confidence: 99%
“…While the literature on the relationship between postural instability and motion sickness is extensive, there is some debate on the exact nature of the relationship. Some studies suggest postural predictors of motion sickness exist in movements recorded before participants are exposed to motion stimuli of any kind (e.g., [26]- [27], [41]- [47]). However, other studies suggest instead that changes in sway occur at the same time as motion sickness onset [8], [48]- [49].…”
Section: Discussionmentioning
confidence: 99%